Value of Computed Tomography ysterosalpingography in Infertile Patients (Journal of Academic Research, 2023)
Infertility is a common health problem requiring imaging to delineate the anatomical causes in women. Computed tomography hysterosalpingography (3D-MDCT-HSG) offers an easy workup for uterine, tubal and peritoneal factors. The purpose of this study was to evaluate the role of 3D-MDCT-HSG in infertile women with the objectives to present the spectrum of uterine, tubal and peritoneal findings and to assess the diagnostic accuracy of it. A study was conducted on 50 infertile women with non-diagnostic HSG from February 2022 to January 2023. Sixty four slice MDCT acquired the scan by contrast instillation into uterine cavity. The result shows that 3D-MDCT-HSG can detect various factors responsible for female infertility especially tubal and uterine; in cases where HSG fails to clearly delineate the pathology
Keywords: HSG; H ysterosalpingography; 3D-MDCT-HSG; Three dimensional multidetectorcomputed tomography; hysterosalpingography